Adipose Tissue in the Filum Terminale: A Computed Tomographic Finding That May Indicate Tethering of the Spinal Cord - Roger E. McLendon; Jerry Oakes; R Heinz; A E Yeates; Peter C. Burger (1988)
Abstract Adipose tissue in the filum terminale is frequently associated with tethering of the spinal cord in patients with spina bifida occulta (3, 8). We recently saw a patient with low back pain and no spina bifida occulta, in whom adipose tissue was noted in the area of the filum on an unenhanced computed tomographic (CT) scan. The patient had a tethered cord. This case suggested that, when CT scanning is done as the first imaging study in the evaluation of low back pain, fatty tissue in the area of the filum may be an indicator for tethering of the spinal cord. The present study was undertaken to determine the validity of using CT scan-detectable filal fat in the identification of possible tethered spinal cords among a group of patients experiencing low back pain. The presence of fat in the fila of 12 patients with the radiologically and histologically tethered cord syndrome was evaluated and the fila of 47 autopsied patients whose clinical history showed no back pain were examined histologically. There were accumulations of adipose tissue in the fila of 11 of the 12 (91%) patients with the tethered cord syndrome and in the fila of 9 of the 47 patients (17%) in the autopsy series. Of the 9 autopsy patients with fat in their fila, however only 3 patients (6%) exhibited collections of adipose tissue in the CT detection range (2 mm). These results demonstrate that, although CT scan-detectable adipose tissue can be found in the filum of an occasional patient without tethered cord, CT detectable fat in the filum of a patient with low back pain should prompt an evaluation for a tethered spinal cord. CT scanning has potential as a noninvasive tool in such a work-up.